Characterization of biodiesel produced from multiple feedstocks for sustainable production of agro-based fuels - Razali, Muhammad Amirul Ashraf; Ahmad, Farah; Hassan, Masjuki (Springer, 2024)
In this study, biodiesel was derived from multiple vegetable oils mixed with palm oil. Transesterification of vegetable oil was performed using methanol and alkaline catalyst (potassium hydroxide (KOH)) at varying temperature (50–70 °C). The resulting biodiesel or fatty acid methyl esters (FAME) was evaluated for its chemical bonds and different FAME composition, in which the results from the latter were used to determine its fuel properties. The physico-chemical properties of biodiesel from multiple feedstocks were analyzed empirically for calorific value, cetane number, density, and kinematics viscosity. Biodiesel produced exhibited improved performance in some fuel properties in comparison to biodiesel prepared from single vegetable oil feedstock, especially for cetane number values and kinematic viscosity.